Gays and Lesbians Parenthood: the emergence of the issue in Argentine - Libson, Micaela (2014)
Th is article describe the emergence of gays and lesbians paranthood’s issue. We analyses two processes: the politization of the theme by the activism LGTTBI and the academic debate. We take these cases: United States, England, France and Spain.